Optimisation in plant operations for a 100 MW Central Receiver CSP plant with focus on the plant operating strategies. - De Meyer, Oelof Abraham Jakobus (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.